Peripartal rumen-protected methionine supplementation to higher energy diets elicits positive effects on blood neutrophil gene networks, performance and liver lipid content in dairy cows. Issue 1 (December 2016) - Li, Cong; Batistel, Fernanda; Osorio, Johan; Drackley, James; Luchini, Daniel; Loor, Juan
Abstract Background Main objectives were to determine to what extent Smartamine M (SM) supplementation to a prepartal higher-energy diet could alter neutrophil (PMN) and liver tissue immunometabolic biomarkers, and whether those responses were comparable to those in cows fed a prepartal lower-energy diet (CON). Results Twenty-eight multiparous Holstein cows were fed CON (NEL  = 1.24 Mcal/kg DM) during d −50 to d −22 relative to calving. From d −21 to calving, cows were randomly assigned to a higher-energy diet (OVE, n  = 9; NEL  = 1.54 Mcal/kg DM), OVE plus SM (OVE + SM, n  = 10; SM = 0.07 % of DM) or remained on CON (n  = 9). All cows received the same basal lactation diet (NEL  = 1.75 Mcal/kg DM). Supplementation of SM (OVE + SM) continued until 30 d postpartum. Liver biopsies were harvested at d −10, 7, and 21 relative to parturition. Blood PMN isolated at −10, 3, and 21 d relative to calving was used to evaluate gene expression. As expected, OVE increased liver lipid content postpartum; however, cows fed OVE + SM or CON had lower concentrations than OVE. Compared with OVE, cows in CON and OVE + SM had greater DMI postpartum and milk production. Furthermore, cows fed OVE + SM had the greatest milk protein and fat percentage and lowest milk SCC despite having intermediate PMN phagocytic capacity. Adaptations in PMN gene expression in OVE + SM cows associated with the lower SCC were gradual increases from −10 to 21 d in genes that facilitate migration into inflammatory sites (SELL, ITGAM ), enzymes essential for reducing reactive oxygen metabolites (SOD1, SOD2 ), and a transcription factor(s) required for controlling PMN development (RXRA ). The greater expression ofTLR4 on d 3, key for activation of innate immunity due to inflammation, in OVE compared with CON cows suggests a more pronounced inflammatory state. Feeding OVE + SM dampened the upregulation ofTLR4, despite the fact that these cows had similar expression of the pro-inflammatory genesNFKB1 andTNF as OVE. Cows in CON had lower overall expression of these inflammation-related genes andGSR, which generates reduced glutathione, an important cellular antioxidant. Conclusions Although CON cows appeared to have a less stressful transition into lactation, SM supplementation was effective in alleviating negative effects of energy-overfeeding. As such, SM was beneficial in terms of production and appeared to boost the response of PMN in a way that improved overall cow health.